2016
DOI: 10.1186/s12974-016-0564-0
|View full text |Cite
|
Sign up to set email alerts
|

A possible role of microglia-derived nitric oxide by lipopolysaccharide in activation of astroglial pentose-phosphate pathway via the Keap1/Nrf2 system

Abstract: BackgroundToll-like receptor 4 (TLR4) plays a pivotal role in the pathophysiology of stroke-induced inflammation. Both astroglia and microglia express TLR4, and endogenous ligands produced in the ischemic brain induce inflammatory responses. Reactive oxygen species (ROS), nitric oxide (NO), and inflammatory cytokines produced by TLR4 activation play harmful roles in neuronal damage after stroke. Although astroglia exhibit pro-inflammatory responses upon TLR4 stimulation by lipopolysaccharide (LPS), they may al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 95 publications
0
66
0
1
Order By: Relevance
“…Of note, the functional activation of neurons increases glucose utilization locally, and both neurons and astroglia contribute to glucose consumption. We have focused on the roles of glucose metabolism, especially glycolysis in astroglia, from the perspective of their supportive aspects in the protection of neurons against oxidative stress . Neuronal energy production is dependent on mitochondrial oxidative metabolism, which produces small amounts of reactive oxygen species (ROS).…”
Section: Glucose and Lacatementioning
confidence: 99%
See 2 more Smart Citations
“…Of note, the functional activation of neurons increases glucose utilization locally, and both neurons and astroglia contribute to glucose consumption. We have focused on the roles of glucose metabolism, especially glycolysis in astroglia, from the perspective of their supportive aspects in the protection of neurons against oxidative stress . Neuronal energy production is dependent on mitochondrial oxidative metabolism, which produces small amounts of reactive oxygen species (ROS).…”
Section: Glucose and Lacatementioning
confidence: 99%
“…Neuronal energy production is dependent on mitochondrial oxidative metabolism, which produces small amounts of reactive oxygen species (ROS). Oxidative stress has been implicated in the pathogenesis of numerous neurological disorders (i.e., stroke, ALS, Parkinson's disease) as well as normal aging of the brain . The glutathione system acts as an intrinsic protective mechanism.…”
Section: Glucose and Lacatementioning
confidence: 99%
See 1 more Smart Citation
“…The detoxifying enzymes, glutathione synthetase and peroxiredoxins activated and released by the Keap1/Nrf2 pathway, protect cells against oxidative stress and maintain homeostasis [13][14][15]. This study demonstrated that LBP upregulated the mRNA and protein levels of Keap1, Nrf2 and HO-1 in liver and kidney in the co-CH group.…”
Section: Discussionmentioning
confidence: 62%
“…Long-term chemotherapy causes oxidative damage, which reduces the levels and capacities of antioxidant enzymes. The resultant oxidative stress may decrease immunity and enhance adverse chemotherapy reactions [13][14][15]. The Kelch-like ECH-associated protein 1 (Keap1)/nuclear factor-erythroid-2-related factor 2 (Nrf2) system, which is the master regulator of the anti-stress response, induces the activities of various enzymes via Nrf2-mediated transcriptional regulation under stress conditions [16].…”
Section: Introductionmentioning
confidence: 99%